High-power waveguide resonator second harmonic device with external conversion efficiency up to 75%. (14th May 2018) - Stefszky, M; Ricken, R; Eigner, C; Quiring, V; Herrmann, H; Silberhorn, C
Abstract: We report on a highly efficient waveguide resonator device for the production of 775 nm light using a titanium indiffused LiNbO3 waveguide resonator. When scanning the resonance, the device produces up to 110 mW of second harmonic power with 140 mW incident on the device—an external conversion efficiency of 75%. The cavity length is also locked, using a Pound–Drever–Hall type locking scheme, involving feedback to either the cavity temperature or the laser frequency. With laser frequency feedback, a stable output power of approximately 28 mW from a 52 mW pump is seen over one hour.